Making Direct Democracy Work. An economic perspective on the graphe paranomon in ancient Athens - Carl Hampus Lyttkens; George Tridimas; Anna Lindgren (Lund University, School of Economics and Management, Department of Economics, 2017)
The specific way the Athenians set up their democracy presents both theoretical and empirical challenges. Decisions were taken by majority vote in the Assembly. To keep politicians in line, the Athenians first used ostracism, which however was replaced by the graphe paranomon around 415 BCE. The latter provided that anybody who had made a proposal in the Assembly could be accused of having made an unconstitu¬tional suggestion, bringing a severe penalty if found guilty. We know of 35 such cases between 403 and 322. During the fourth century the notion of illegality was extended to a mere question of undesirability. Henceforth any decision by the Assembly could be overturned by the courts, but if the accuser failed to get at least 20% of the jury votes, he was punished instead. While these rules can be seen as a safeguard against bad decisions, they also provided the Athenian politicians with important information about the relative strength of their political support. This effect has not been analysed before, and it may help explain the relative stability of political life in classical Athens. Furthermore this analysis also contributes to our understanding of a curious but often overlooked fact, namely that the decrees of the Athenian Assembly to a great extent concerned honorary rewards, and the use of the graphe paranomon in turn was largely focussed on the honorary decrees.
Keywords: H10; N40; N43; 330; Ancient Athens; graphe paranomon; direct democracy; judicial review; voter; information; political stability; jury composition